Modelling the economic and environmental impacts of water resources in the context of climate neutrality in the EUSDR member states - Ionescu, Romeo Victor; Zlati, Monica Laura; Antohi, Valentin Marian; Cristea, Dragoș Sebastian; Petrea, Ștefan Mihai; Forțea, Costinela (Frontiers in Environmental Science, 2024)
In the context of the objective of climate neutrality at the European level, this scientific approach analyses the modelling of the economic and ecological impact of water resources at the level of the Member States (Bulgaria, Czechia, Germany, Croatia, Hungary, Austria, Romania and Slovakia) of EU Strategy for the Danube Region (EUSDR). The objectives of the research are to study climate protection models presented in the literature as a basis for a dynamic model of the economic and ecological impact of water resources in the context of climate neutrality. The methods used consist of a study of the literature, the construction and analysis of a database of relevant indicators for which econometric procedures are then applied to test and validate a dynamic impact model. The results of the study will highlight the potential vulnerability in reaching the Green Deal targets on the two horizons 2030 and 2050 proposed by the EU, as well as the impact of the blue economy in reaching these targets.